The Rule of Nicolae Ceausescu and Its Tragic Episode during the Romanian December Revolution - Sporea, Danijel G. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In December 1989, thousands of Romanian citizens took to the streets, protesting against Nicolae Ceausescu’s policies. This was no surprise—some time ago, the Warsaw Pact countries, which for decades languished in the ideology of communism and the one-party system, struggled to put this era behind them. These uprisings initiated the fall of the current regimes through initial protests, which was why the then political elite often responded hysterically with repression and political violence. As the last country from the Central-Eastern bloc, Romania started the changes in the most repressive way and ended the era of communism. The most impressive aspect of this transition is the behaviour of Nicolae Ceausescu, the president of Romania at that time, who ignored the mentioned events in the neighbourhood. The initial revolt of the Romanian people, which Ceausescu visibly defied without suspecting that it would affect him, finally happened and closed his rule in blood. Relying on a wide range of different sources of material, in this paper we will try to present the historiography of the Romanian revolution authentically, from the perspective of the present moment. The starting point for the work is a conceptual analysis of the rule of Nicolae Ceausescu—from the very beginning, through the characteristic periods, all the way to the year of its completion. His rule, characterized by other Warsaw Pact states as the most severe form of communism, led to violence and revolutionary riots that left a bloody mark on Romania’s history. Some of the theses presented, such as the coup d’etat, conspiracy, or foreign intervention, which were presented as the cause of the collapse of Ceausescu’s regime, opened space for many reflections. But the real picture seems much simpler: the people of Romania, after the most difficult period of austerity, poverty, and torture, rose against a dictatorial regime that has denied the most basic social and humanistic values.
Keywords: Romania; communism; Nicolae Ceausescu; dictatorship; December 1989; protests; revolution